PENGARUH DAYA TARIK WISATA TERHADAP MINAT BERKUNJUNG WISATAWAN DI GALERI NASIONAL INDONESIA - Wijaya, Sherren; Ardiansyah, Imam (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2023)
This study aims to determine the effect of attractiveness on tourist interest in the National Gallery of Indonesia. The object of this research is people who are visiting the National Gallery of Indonesia. The research sample amounted to 100 people used by purposive sampling method. All data were processed using the SPSS (Statistical Program for Social Science) version 25.This research uses quantitative methods. In this study the results showed that the t value of the variable count Attraction (X1) amounted to 3.454> t table (1.984) with a value of Sig. 0.001 <0.05 then H0 is rejected and HA is accepted so that it can be concluded that Attraction (X1) has a positive influence on Interest in Visiting at the National Gallery of Indonesia.The t value of the Amenity variable (X2) is -0.46> t table (1.984) with a Sig value. 0.963 <0.05, then H0 is accepted and HA is rejected so it can be concluded that the Attractiveness of Amenities (X2) has no effect on Interest in Visiting at the National Gallery of Indonesia. t value of the Accessibility variable (X3) is 2.108> t table (1.984) with a Sig value. 0.038 <0.05 then H0 is rejected and HA is accepted so it can be concluded that Accessibility Attraction (X3) has a positive influence on Interest in Visiting at the National Gallery of Indonesia.